Optimizing Liquefied Natural Gas (LNG) Supply Chains: An Operational Efficiency Analysis of Floating LNG Facilities in Cameroon - Eyong, Obi Carlos (Yayasan Gema Bina Nusantara, 2025)
This research investigates the impact of digital transformation strategies on the operational performance of Cameroon’s domestic gas distribution sector. As digitalization reshapes data-driven industries, gas organizations in emerging markets face unique challenges in integrating advanced information systems. Utilizing a quantitative approach with Structural Equation Modeling (SEM), this study analyzes how digital leadership, infrastructure readiness, and knowledge management influence distribution efficiency. The findings reveal that while technological adoption significantly reduces operational losses and enhances data accuracy, its success is heavily contingent on the holistic integration of human resources and financial management. Despite persistent infrastructural constraints in Cameroon, strategic digitalization provides a critical roadmap for operational resilience, ensuring more reliable energy delivery and improved safety standards across the national industrial landscape.